Terapi Bekam Basah Terhadap Penurunan Kadar Asam Urat Dalam Darah: Tinjauan Pustaka: Wet Cupping Therapy for Reducing Uric Acid Levels: Literatur Review - Arif Tirtana; Muhammad Habib (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Uncontrolled uric acid on blood can lead to hyperuricemia in a person. Many symptoms shown when a person suffer gout were inflammation, pain, heat, swollen and stiff joints so it cannot move as usual. The morbidity rate of patients at the age of 34 years was 32% and aged over 34 years was 68%. One of the solutions that can be offered to reduce the symptoms of gout is by treating was removing static blood that contains toxins from the human body. The research aim was to determine the effect of wet cupping on reducing uric acid levels in the blood. The method that used on this research was Problem Intervention Comparison Outcome Study design (PICOS) framework. The selection of articles with the keywords